Pharmacokinetics of oral terbinafine in adult horses - Younkin, Jarrod T. (Kansas State University, 2018)
The primary study objective was to compare the pharmacokinetics of p.o. terbinafine alone to p.o. terbinafine administered with p.o. cimetidine in healthy adult horses. The second objective was to assess the pharmacokinetics of terbinafine when administered per rectum in two different suspensions at 30 mg/kg to adult horses. Six healthy adult horses were included in this crossover study. Plasma terbinafine concentrations were quantified with liquid chromatography and mass spectrometry. The half-life (geometric mean) was 8.38 and 10.76 h, for p.o. alone and p.o. with cimetidine, respectively. The mean maximum plasma concentrations were 0.291 lg/mL at 1.54 h and 0.418 lg/mL at 1.28 h for p.o. alone and p.o. with cimetidine, respectively. Terbinafine with cimetidine had an average CMAX 44% higher and the relative F was 153% compared p.o. terbinafine alone but was not statistically different (P > 0.05). Terbinafine was infrequently detected when administered per rectum in two different suspensions (water or olive oil). Minor adverse effects included oral irritation, fever, and colic. All resolved spontaneously. More pharmacokinetic studies are indicated assessing drug–drug interactions and using multiple dosing intervals to improve our knowledge of effective oral dosing, the potential for drug accumulation, and systemic adverse effect of terbinafine in horses.
Keywords: Horse; Equine; Terbinafine; Anti-fungal; PharmacokineticsDrug